Studi Kasus : Analisis Kesulitan Membaca Pada Siswa Kelas V SD Muhammadiyah Kranggan - Rahman, Muhammad Arif; Primadoni, Ade Bagus; Santoso, Yan Imam (Universitas Muhammadiyah Magelang, 2024)
This research aims to determine the factors behind students experiencing difficulties in reading in class V of SD Muhammadiyah Kranggan. The research method used is a qualitative method with a case study approach. The subjects of this research were V grade students who had difficulty reading, 5 students out of a total of 15 students, class teachers and parents who were also respondents in this research. This research was conducted in July of the 2022–2023 academic year. Students, teachers and parents will be interviewed and observed as data sources for data collection in this research. Based on the findings in this research, there are internal and external factors that contribute to students' reading difficulties. The internal factors are physiological, cognitive and psychological. Meanwhile, external factors are parents, educators and the environment.